Do Small Molecules Activate the TrkB Receptor in the Same Manner as BDNF? Limitations of Published TrkB Low Molecular Agonists and Screening for Novel TrkB Orthosteric Agonists - Piotr Pankiewicz; Marcin Szybiński; Katarzyna Kisielewska; Filip Gołębiowski; Patryk Krzemiński; Izabela Rutkowska-Włodarczyk; Rafał Moszczyński-Pętkowski; Lidia Gurba-Bryśkiewicz; Monika Delis; Krzysztof Mulewski; Damian Smuga; Jakub Dominowski; et al. (MDPI AG, 2021)
TrkB is a tyrosine kinase receptor that is activated upon binding to brain-derived neurotrophic factor (BDNF). To date, the search for low-molecular-weight molecules mimicking BDNF's action has been unsuccessful. Several molecules exerting antidepressive effects in vivo, such as 7,8-DHF, have been suggested to be TrkB agonists. However, more recent publications question this hypothesis. In this study, we developed a set of experimental procedures including the evaluation of direct interactions, dimerization, downstream signaling, and cytoprotection in parallel with physicochemical and ADME methods to verify the pharmacology of 7,8-DHF and other potential reference compounds, and perform screening for novel TrkB agonists. 7,8 DHF bound to TrkB with Kd = 1.3 μM; however, we were not able to observe any other activity against the TrkB receptor in SN56 T48 and differentiated SH-SY5Y cell lines. Moreover, the pharmacokinetic and pharmacodynamic effects of 7,8-DHF at doses of 1 and 50 mg/kg were examined in mice after i.v and oral administration, respectively. The poor pharmacokinetic properties and lack of observed activation of TrkB-dependent signaling in the brain confirmed that 7,8-DHF is not a relevant tool for studying TrkB activation in vivo. The binding profile for 133 molecular targets revealed a significant lack of selectivity of 7,8-DHF, suggesting a distinct functional profile independent of interaction with TrkB. Additionally, a compound library was screened in search of novel low-molecular-weight orthosteric TrkB agonists; however, we were not able to identify reliable drug candidates. Our results suggest that published reference compounds including 7,8-DHF do not activate TrkB, consistent with canonical dogma, which indicates that the reported pharmacological activity of these compounds should be interpreted carefully in a broad functional context.